Analysis of Migration Determinants in Java Island: A Panel Data Analysis - Aisyah, Siti; Atmojo, Agung Tri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Migration as in internal or international is a very important poin to consider in regional development planning due to its strong connection to government attempts in improving welfare distribution among its people. This study aimed to analyze the effect of Regional Minimum Wages (UMP), Gross Regional Domestic Product (GRDP), investment, and government spending on in- migration to provinces in Java Island. This study utilized a panel data regression model from 1995 – 2015 in six provinces in Java Island using Fixed Effect Model (FEM). The data was obtained from Statistic Indonesia and Indonesian Investment Coordinating Board. The results showed that the Regional Minimum Wage (UMP) and investment had a positive impact on in-migration, while GDRP was proven to have a negative impact. On the other hand, government expenditure sis not have any effect on in-migration.To cope with the high rate of population movement or migration, the government should take policies such as allocating and increasing investment outside of large, densely populated cities and industries in order to support economic growth and increase production capacity which will increase wages, thereby reducing population movement or migration to big cities.